Preparation of polypropylene filter incorporated with titanium dioxide and reduced graphene oxide for real water treatment - Ibrahim, Izwaharyanie; Lim, Hong Ngee; Sharifuddin, Syazrin Syima; M. Yusof, Muhammad Azroie; Huang, Nay Ming; Pandikumar, Alagarsamy (American Scientific Publishers, 2015)
Herein, we report the hydrothermal preparation of a reduced graphene oxide/titanium dioxide incorporated porous polypropylene (PP-RGO/TiO2) filter for water treatment application. The as-prepared PP-RGO/TiO2 filter was characterized by Raman and Field Emission Scanning Electron Microscopy (FESEM) analyses. The Raman spectra suggested the successful reduction of GO to RGO and the incorporation of TiO2 into the RGO sheets. The photocatalytic activity of the PP-RGO/TiO2 filter was investigated in relation to the degradation of methylene blue (MB), and it showed complete degradation of MB after illumination by a halogen lamp for 2 h. Further, this PP-RGO/TiO2 filter was used for the treatment of real lake water. The dissolved oxygen (DO) of the lake water after being treated with the PP-RGO/TiO2 filter in the presence of ultraviolet (UV) irradiation showed great reductions of 7.5, 14, and 24% for the first, second, and third cycles, respectively. The chemical oxygen demand (COD) of the lake water was effectively decreased to 43, 27, and 16% in successive cycles by the PP-RGO/TiO2 filter with the assistance of UV. Moreover, a good reduction in the NH3–N concentration was also shown in lake water when it was treated under the same condition as the DO, with an increase in the ammonia removal of >27%. The PP-RGO/TiO2 filter maintained its ability to remediate wastewater even after three cycles of treatment.